Prioritizing development policy research in Egypt: An innovative approach to inform IFPRI’s Egypt Strategy Support Program - Abdelaziz, Fatma; Al-Riffai, Perrihan; Breisinger, Clemens; Dorosh, Paul A.; Ecker, Olivier; ElDidi, Hagar; El-Enbaby, Hoda; Figueroa, Jose Luis; Kenawy, Laila; Leroy, Jef L.; Minot, Nicholas; Spielman, David J.; et al. (International Food Policy Research Institute, 2016)
This paper presents an innovative approach to prioritizing development policy research in Egypt with the specific objective of informing the research agenda of the Egypt Strategy Support Program of the International Food Policy Research Institute. The key steps in this process were: 1) a review of relevant priority setting methods and existing government strategies, 2) pre-selection of research themes, 3) selection of national and international experts, 4) design and conduct priority setting workshop; and 5) priority matrix construction and paper writing.